Spatial-temporal variation and influencing factors of ecological environment quality in Jilin Province (China) - Wang, Feiyu; Han, Yang; Xu, Yaping; Zhu, Ruifei; Qu, Chunmei; Zhang, Peng; Martin, Stanton; Zhuang, Lijuan; Liu, Zhuxin; Zhang, Jiani; Huang, Fang (Frontiers in Environmental Science, 2024)
Jilin Province is a crucial region of interest for agricultural and forestry development in China. The deterioration of its ecological environment could have a severe impact on agricultural production and ecological conservation. A systematic assessment of ecological environment quality in Jilin Province is essential for its sustainable development. In this study, we utilized Landsat data from 1990 to 2020 (every five years) to construct the Remote Sensing Ecological Index (RSEI) for Jilin Province. We applied the Sen's slope estimator and the Mann-Kendall trend test to examine the spatiotemporal changes in ecological environment quality over a 30-year period. Additionally, we employed the Geo-detector to explore the socioeconomic and natural factors influencing ecological environment quality. The results revealed: (1) From 1990 to 2020, the average RSEI index in Jilin Province ranged from 0.586 to 0.699, indicating overall good ecological environment quality. Spatially, ecological environment quality gradually declined from east to west. (2) The RSEI in Jilin Province exhibited an initial increase, followed by a decrease, and then another increase trend. This improvement can be attributed to the implementation of government policies, which reversed the expansion of salinealkali land. Ecological environment quality significantly improved in the western region of Jilin Province over the 30-year period. (3) Socioeconomic and natural factors both influence ecological environment quality in Jilin Province. Among these factors, vegetation coverage has the most significant impact on the ecological environment quality in the study area, with natural factors exerting a more significant influence than socioeconomic factors.